Desarrollo de una herramienta informática que permita determinar los tiempos de operación, curvas de operación y coordinación de los relés de sobre corriente en las líneas de transmisión - Peralvo Peralvo, Henrry Alexander (2023)
The present research work was mainly focused on the development of a computer tool that allowed to determine the operation times, operation curves and coordination of the overcurrent relays in the transmission lines, the tool is a graphical interface made in the Python Software with the Visual Studio Code interpreter communicated directly with the DIgSILENT PowerFactory software, a start window was developed where the user entered the address and the version of the case study program, later the communication between these was verified with the reading of components and data of our electrical system.